2018
DOI: 10.3390/ijms19051516
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature Changes on Serum Protein Adsorption on Thermoresponsive Cell-Culture Surfaces Monitored by A Quartz Crystal Microbalance with Dissipation

Abstract: Thermoresponsive cell-culture polystyrene (PS) surfaces that are grafted with poly(N-isopropylacrylamide) (PIPAAm) facilitate the cultivation of cells at 37 °C and the detachment of cultured cells as a sheet with an underlying extracellular matrix (ECM) by reducing the temperature. However, the ECM and cell detachment mechanisms are still unclear because the detachment of cells from thermoresponsive surfaces is governed by complex interactions among the cells/ECM/surface. To explore the dynamic behavior of ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 48 publications
2
24
0
Order By: Relevance
“…Thus, the silk fibroin spectra showed four secondary C 1s peaks: a first peak centered at about 284.51 eV, corresponding to C-C; a second peak centered at 285.25 eV, which can be assigned to C-H (CH 3 in alanine; -CH 2 - and -CH- in backbone); a third peak centered at 286.12 eV, which can be assigned to C-O/C-N; and a fourth peak centered at 287.96 eV, which can be assigned to C=O/N-C=O [34]. The C 1s spectra of PNIPAM revealed four peaks: a first peak centered at about 284.97 eV, assigned to C-C contribution, and three deconvoluted peaks centered at 285.92, 287.05 and 288.16 eV, assigned to multiple C-H groups, C-O/C- and C=O/N-C=O, respectively [35,36]. The C 1s spectra of SF-g-PNIPAM (0.1 w / w to SF) also revealed four peaks shifted to lower values with respect to the silk fibroin spectrum: the first peak was centered at about 283.98 eV, which can be assigned to C-C, with the contribution of a new carbon species from PNIPAM structures [35,36].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the silk fibroin spectra showed four secondary C 1s peaks: a first peak centered at about 284.51 eV, corresponding to C-C; a second peak centered at 285.25 eV, which can be assigned to C-H (CH 3 in alanine; -CH 2 - and -CH- in backbone); a third peak centered at 286.12 eV, which can be assigned to C-O/C-N; and a fourth peak centered at 287.96 eV, which can be assigned to C=O/N-C=O [34]. The C 1s spectra of PNIPAM revealed four peaks: a first peak centered at about 284.97 eV, assigned to C-C contribution, and three deconvoluted peaks centered at 285.92, 287.05 and 288.16 eV, assigned to multiple C-H groups, C-O/C- and C=O/N-C=O, respectively [35,36]. The C 1s spectra of SF-g-PNIPAM (0.1 w / w to SF) also revealed four peaks shifted to lower values with respect to the silk fibroin spectrum: the first peak was centered at about 283.98 eV, which can be assigned to C-C, with the contribution of a new carbon species from PNIPAM structures [35,36].…”
Section: Resultsmentioning
confidence: 99%
“…4(C), lower]. Previous reports indicated that no fibronectin was released from PIPAAm or heparin-immobilized poly(IPAAm-co-CIPAAm) surfaces on which cells were not cultured after reducing temperature to 20 C. 37,52 These imply that the pulling force that is generated by the contraction of stress fibers is essential for the detachment of fibronectin and bFGF, which are bound with receptors through affinity (e.g., K D between a fibronectin fragment and an integrin α 5 β 1 , 4.4 nM 53 and that between bFGF and FGFR1, 61.9 nM). 49 HB-EGF-bound heparin-immobilized temperature-responsive surfaces facilitate the fabrication of hepatocyte sheets with preserved hepatic functions.…”
Section: Acceleration Of Cell Sheet Preparationmentioning
confidence: 99%
“…Coatings based on thermoresponsive polymers consistently prove to be a valuable foundation for cell sheet engineering purposes [ 1 , 2 , 3 ]. Due to their physical response to changes in temperature under aqueous conditions, such coatings can switch from a rather hydrophobic, protein- and cell-adhesive state into a more hydrophilic, protein- and cell-repellant state upon cooling [ 4 , 5 ]. This phase transition is characterized by an increase in coating hydration, which is usually accompanied by the swelling of the thermoresponsive polymer layer.…”
Section: Introductionmentioning
confidence: 99%